A comparison between static load test and high strain dynamic test on bored piles - 266602 Michael Angelo Murugun@Arokiasamy (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Kejuruteraan (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2006